BUDAYA KERJA KEPALA DESA DALAM PELAYANAN MASYARAKAT DI DESA MASSENRENGPULU KABUPATEN BONE - Nurfadilla, Nurfadilla; Malik, Ihyani; Wahid, Nur (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
This research aims to determine the work culture of village heads in community services in Masserengpulu Village, Bone Regency. Very influential in improving community services, as well as helping identify areas that need improvement and creating strategies to build a healthy and positive work culture. The research method used is a naturalistic research method with a qualitative approach. Data was obtained through interviews and document analysis to understand the work culture of village heads in community services. The results of the research show that the Village Head's work culture in community services in Massenrengpulu Village, Bone Regency is still lacking in discipline due to staff who are still irregular in their working hours, the implementation of the Village Head's openness principle, there is deliberation in resolving problems, mutual respect is still lacking and the Village Head's cooperation is still lacking, because the Village Head rarely shows himself at the village office when meetings are held, which is a form of failure in building an effective cooperative nature, this hampers the improvement of services which will ultimately affect the quality of services provided to the community.